Designing the Safe Reopening of US Towns Through High‐Resolution Agent‐Based Modeling. Issue 9 (1st August 2021) - Truszkowska, Agnieszka; Thakore, Malav; Zino, Lorenzo; Butail, Sachit; Caroppo, Emanuele; Jiang, Zhong‐Ping; Rizzo, Alessandro; Porfiri, Maurizio
Abstract: As COVID‐19 vaccine is being rolled out in the US, public health authorities are gradually reopening the economy. To date, there is no consensus on a common approach among local authorities. Here, a high‐resolution agent‐based model is proposed to examine the interplay between the increased immunity afforded by the vaccine roll‐out and the transmission risks associated with reopening efforts. The model faithfully reproduces the demographics, spatial layout, and mobility patterns of the town of New Rochelle, NY — representative of the urban fabric of the US. Model predictions warrant caution in the reopening under the current rate at which people are being vaccinated, whereby increasing access to social gatherings in leisure locations and households at a 1% daily rate can lead to a 28% increase in the fatality rate within the next three months. The vaccine roll‐out plays a crucial role on the safety of reopening: doubling the current vaccination rate is predicted to be sufficient for safe, rapid reopening. Abstract : As COVID‐19 vaccine is rolling out, the economy is gradually reopening. This study offers scientific backing for the ongoing debate regarding the safety of reopening efforts via a high‐resolution computational model of a US town. Computational results suggest that the current vaccination rate can only support careful reopening. A swift return to normalcy would require at least doubling the vaccination speed.